PIJAT BAYI TERHADAP STATUS GIZI BALITA - Intan Arum Anjar Wati; Nurul Fatimah; Sholihah Gustavia Yolanda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Nutritional status of toddlers is an important indicator of child health quality. One non-pharmacological intervention to improve nutritional status is infant massage. Infant massage can stimulate digestion, increase appetite, and improve metabolism. This study aimed to determine the effect of infant massage on the nutritional status of toddlers. This study used a quantitative method with a pre-experimental (one group pretest-posttest) design. The sample consisted of 35 toddlers selected using purposive sampling. Data were collected through weight measurements before and after the intervention. Data were analyzed using paired t-test. The results showed a significant improvement in nutritional status after infant massage with a p-value of 0.001. In conclusion, infant massage has a significant effect on improving the nutritional status of toddlers.